IMPLEMENTASI HYBRID LEARNING MENGGUNAKAN APLIKASI EDMODO PADA MATAKULIAH METODE PENELITIAN KUALITATIF - Muhammad Sulistiono (Universitas Islam Malang, 2019)
This article discusses the application of Hybrid Learning using the Edmodo application in the subject of the qualitative research method for fourth semester students at Podi PGMI UNISMA Malang. The discussion chapter is divided into three sub-topics. First is online lecture planning in qualitative research courses. Starting from semester learning plans, learning strategies and material preparation in the form of soft files, so that they are easily uploaded and downloaded by lecturers and students. The second is the implementation of online lectures in qualitative research courses. For some online college students it is new but for most online college students it is new. The difficulties and advantages of online ducting appear on each side. One of the difficulties associated with technical matters is understanding material and collecting tasks. From an excess point of view, one of them is that students no longer print assignments so they are more efficient because there are no printing costs for lecture assignments. The three Edmodo assessments provide a variety of assignment models ranging from file delivery assignments, choice of gandan, essay, match, and incorrect. In addition, the value of learning outcomes is better controlled because each task file, Edmodo provides an assessment form. So that students are able to know the assessment transparently. And if something goes wrong, students and lecturers can monitor each other while conducting joint evaluations.